BODY OF JOGET ALE-ALE AS CAPITAL OF RESISTANCE - Alfarisi, Salman (E-Journal of Cultural Studies; Volume 7, Number 3, Agustus 2014)
This paper aims to understand how the phenomenon of the dancing body art Ale - ale. This art appears in the middle of the Sasak , Lombok , 1999. The three elements of this art , the music , song , and dance reflects the idea of resistance against the establishment . Demolition of the single truth Tuan Guru and cultural as the dominant group in society Sasak looked at the expression of dance dancing . Therefore , to understand the dimensions of the dancing resistance used qualitative - interpretative methods research design paradigm of cultural studies . The theory used is critical social theory , such as social practice theory of Bourdieu , Derrida deconstruction theory , and postmodern aesthetics in addition . Data acquisition is done by in-depth interviews , observation paratisipatoris , and documentation . An important finding of this study include first , dancing body memerlihatkan wealth dimensional art Ale - ale resistance due to the body , dancing can liberate ourselves from the reality of their urgency , urgency both in economic and social dimensions is constructed by an elite group of Sasak community . In this context , the body dancing is not only a personal expression of dancing , but also can be a practice arena power of dominant groups in society Sasak , namely Mr. Guru and culture . Second , not only the dancing body can be seen as a mere aesthetic expression but as a form of battle between the marginalized groups dancing with the dominant group , namely Mr. Master in religious and cultural problems in the context of culture
Keywords: the body , joget , freedom , resistance